Audit Quality Analysis in Dealing with Auditor Uncertainty: The Role of Independence, Competence and Time Budget Pressure in the Audit Process at the Public Accounting Firm of DKI Jakarta - Tarigan, Krisnawati Br; Juliogracia, Daniel (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
This research aims to analyze the impact of independence, competence, and time budget pressure in the audit process on the quality of audits. The study is designed to determine the effects of the independent variables both individually and collectively on the dependent variable. The sample population includes auditors employed by Public Accounting Firms in the DKI Jakarta region. Through purposive sampling, 104 qualifying respondents were selected. The research utilizes the SPSS 24 software for testing. The findings indicate that (1) Independence positively and significantly affects audit quality, (2) Competence positively and significantly affects audit quality, and (3) Time Budget Pressure in the Audit Process does not affect audit quality.